Development of a Comprehensive HPLC Method for Determination of Product-related Impurities and Assay of Active Ingredients in Papaverine Hydrochloride Products - N. P. Antonova; E. P. Shefer; N. E. Semenova; S. S. Prokhvatilova; A. M. Kalinin; S. A. Kuchugurin; V. N. Makukhin (Регуляторные исследования и экспертиза лекарственных средств, 2021)
Abstract. Papaverine hydrochloride products are used as anticonvulsants in routine medical practice. Most of the approved product specification files include thin-layer chromatography for assessment of product-related impurities and UV spectrophotometry for determination of active pharmaceutical ingredients. An HPLC assay is not used for determination of papaverine hydrochloride in drug dosage forms.The aim of the study was to develop an HPLC test method for determination of product-related impurities and for quantification of papaverine hydrochloride in solutions for injection, tablets, and rectal suppositories.Materials and methods: samples of the following Russian-made papaverine products were used in the study: Papaverine, solution for injection, 20 mg/mL; Papaverine, rectal suppositories, 20 mg; Papaverine, tablets, 40 mg. The Agilent 1260 Infinity II DAD System was used for the HPLC assay, and the Agilent 8453Е UV-Vis System was used for recording UV spectra. The determination of product-related impurities and the assay of active ingredients were performed simultaneously by HPLC using a reversed-phase column Kromasil 100-5-C18, 250×4.6 mm, 5 μm, the gradient elution mode, and detection at        238 nm. Papaverine Hydrochloride USP RS, 99% purity, and Noscapine EP CRS were used as reference standards.Results: the study demonstrated that determination of product-related impurities and assay of active ingredients in papaverine products can be performed simultaneously using HPLC.Conclusions: the authors proposed an HPLC test method for determination of active ingredients in papaverine products, which is aligned with the “consistent standardisation” principle and can be recommended for inclusion into draft monographs for papaverine products.